A Juridical Analysis of Evidence on the Crime of Maltreatment Resulting in Death (Study of Decision Number 35/Pid.B/2018/PN Sbr) - Sendi Ramadhan Mustofa; Gandes Candra Kirana (Faculty of Law, Universitas Trisakti, 2023)
Evidence in the Criminal Procedure Rules is very essential when checking criminal cases in court. The issue raised is whether the evidence in checking criminal acts of abuse which resulted in death is based on the case in the District Court Decision Number 35/Pid.B/2018/PN Sbr which was applied by the public prosecutor appropriately based on the Criminal Procedure Rules Book and whether the action the public prosecutor's failure to provide evidence to the court has legal consequences. This type of research uses normative juridical methods of analytical descriptive nature. The results of the research, discussion and conclusions are seen from the trial in accordance with court decision Number 35/Pid.B/2018/PN Sbr. The Public Prosecutor stated that one of the other witnesses who were related by blood or marriage was mistaken, because it was possible that the statement submitted was not objective. The decision of the District Court in the absence of evidence in the decision Number 35/Pid.B/2018/PN Sbr was a Careless actions are caused by the suspect being acquitted by the prosecutor because the evidence supporting the accusation against the suspect is not strong enough